Nematode larva migrans caused by Toxocara cati in the North Island brown kiwi (Apteryx mantelli). (April 2020) - French, Adrienne F.; Castillo-Alcala, Fernanda; Gedye, Kristene R.; Roe, Wendi D.; Gartrell, Brett D.
Abstract: Sporadic cases of visceral and neural nematode larva migrans have been diagnosed at necropsy in the endangered New Zealand kiwi ( Apteryx spp.), but the causative organisms have not yet been definitively identified. From an initial group of five affected kiwi, PCR was performed on DNA extracted from archival formalin-fixed paraffin-embedded tissue sections in which larval nematodes had been histologically identified. Sequencing of positive results from four out of the five kiwi aligned with sequences from Toxocara cati, a nematode parasite whose definitive host is the domestic cat. PCR was then performed on a second group of 12 kiwi that had histologic inflammatory lesions consistent with larva migrans, but variable larval presence. Repeatable positive PCR results were only achieved in one tissue, in which larval organisms were histologically confirmed. This study supports the use of PCR as an alternative or adjunct to the morphological identification of nematode larvae in formalin-fixed histopathological samples, as well as showing that in investigation of larva migrans, PCR has greatest chance of success from sections where nematode larvae are evident histologically. The identification of Toxocara cati from lesions of larva migrans in kiwi reflects an indirect, parasite-mediated effect of an invasive mammalian species on a native species. Graphical abstract: Image 1 Highlights: Cases of nematode larva migrans have been diagnosed in the New Zealand kiwi. PCR was performed on archival formalin-fixed paraffin-embedded tissue blocks. Results identified Toxocara cati, a parasite of cats, as the causative agent. PCR had greatest success from tissues where larvae were identifiable histologically.